2018
DOI: 10.1063/1.5044629
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Rb in polycrystalline Cu(In,Ga)Se2 layers and effect of Rb on solar cell parameters of Cu(In,Ga)Se2 thin-film solar cells

Abstract: The diffusion of the heavy alkali element rubidium (Rb) in Cu(In,Ga)Se2 (CIGS) layers was investigated over a temperature range from 148 °C to 311 °C by outdiffusion from a rubidium fluoride layer. The diffusion profiles were measured by secondary ion mass spectrometry. By using CIGS layers with different grain sizes, diffusion along grain boundaries could be distinguished from diffusion into the grain interior. Rb was found to diffuse from the CIGS surface along grain boundaries but also within the grain bulk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
54
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 24 publications
8
54
1
Order By: Relevance
“…At the grain boundary, Na is the majority alkali with a Gibbsian interfacial excess (Γ) of 1.5 at nm −2 , compared to 0.5 at nm −2 for K. In the RbF‐treated sample Rb and K are below the detection limit of APT inside the grain whereas Na significantly increases to 39 ppm. In another study, Rb has been found at a very low concentration also inside the grains by time‐of‐flight secondary ion mass spectroscopy . At the grain boundary, even if all alkali elements are found to segregate, Rb is now the majority alkali at the grain boundary with Γ = 1.6 at nm −2 .…”
Section: Effects Of Post‐deposition Treatment With Heavy Alkalismentioning
confidence: 94%
See 1 more Smart Citation
“…At the grain boundary, Na is the majority alkali with a Gibbsian interfacial excess (Γ) of 1.5 at nm −2 , compared to 0.5 at nm −2 for K. In the RbF‐treated sample Rb and K are below the detection limit of APT inside the grain whereas Na significantly increases to 39 ppm. In another study, Rb has been found at a very low concentration also inside the grains by time‐of‐flight secondary ion mass spectroscopy . At the grain boundary, even if all alkali elements are found to segregate, Rb is now the majority alkali at the grain boundary with Γ = 1.6 at nm −2 .…”
Section: Effects Of Post‐deposition Treatment With Heavy Alkalismentioning
confidence: 94%
“…In another study, Rb has been found at a very low concentration also inside the grains by time-of-flight secondary ion mass spectroscopy. [77] At the grain boundary, even if all alkali elements are found to segregate, Rb is now the majority alkali at the grain boundary with Γ = 1.6 at nm −2 . Na and K show an equivalent segregation with Γ = 0.4 at nm −2 .…”
Section: Bulk Effectsmentioning
confidence: 99%
“…It was shown by ab initio calculations that Cu atoms are the most mobile atoms in CISe, whereas In atoms play no role in the mass transport. [41] Experimental findings indicated that heavier AM atoms tend to segregate next to grain boundaries. The vacancymediated diffusion of Na has a larger migration barrier than those of K and Rb, whereas interstitial Na (Na i ) atoms diffuse faster than heavier AM in the interstitial site.…”
Section: Introductionmentioning
confidence: 99%
“…[40] On the other hand, the concentration of K and Rb atoms in the GI is low despite the small migration barriers for the diffusion of the substitutional defects in the absorber layer. [41] Experimental findings indicated that heavier AM atoms tend to segregate next to grain boundaries. [40,42,43] Several studies characterized the positive influences of AM atoms on the cell performance but the underlying reasons are still puzzling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation